Structural modelling and earthquake analysis of a hospital building located within the Tjörnes fracture zone in Iceland - Höskuldur Þorbjargarson 1987- (2016)
The Tjörnes fracture zone(TFZ)is one of the two most active seismic regions in Iceland. It is of vital importance for civil protection and security of the local residents living in that area to have a fully functioning hospital close by, when a major earthquake event occurs within the TFZ. The main focus of this study is to examine the structural characteristics, dynamic behaviour and structural integrity of the hospital in the town of Húsavik in North Iceland. A structural monitoring system was installed in the building in May 2015. The structural monitoring system is a part of the multidisciplinary strong motion array,ICEARRAY II, which is in operation in North Iceland. The measurements have been ongoing for one year and three notable events have occurred that provide useful full-scale records of the building excitation and response and which have been used to determine key dynamic properties and response characteristics as well as for validation of the structural model. A ﬁnite element model was constructed using the structural design software Sap2000 (www.csiberkeley.com). The ﬁrst natural frequency of the building is 7.4 Hz, and the damping ratio at low intensity excitation was found to be of the order, 2 - 3% of critical. Building codes and standard civil engineering practises have evolved considerably since the construction of the hospital in 1964. Especially with regard to seismic design requirements. Individual building components and structural design details will be examined with this in mind. The earthquake excitation used for the analysis is the EN1998-1 Response spectra and records of strong ground motion from earthquake events that occurred in the South Iceland seismic zone in June 2000 and May 2008. The building has many load carrying walls, in a structural system that provides a lot of redundancy. The building deformations are found to be small, or 1 cm or less for a design response spectral analysis. The same can be said about the story drift which is found to be well within the limits ...